Diversity of content and composition of cell wall-derived dietary fibre in polished rice. (November 2020) - Kosik, Ondrej; Romero, Marissa V.; Bandonill, Evelyn H.; Abilgos-Ramos, Riza G.; Sreenivasulu, Nese; Shewry, Peter; Lovegrove, Alison
Abstract: Rice, the staple food of more than half the world's population, is consumed mainly after polishing which removes beneficial components, particularly vitamins, minerals and dietary fibre (DF). Furthermore, the consumption of polished rice and other highly refined foods has been related to high incidences of chronic non-communicable diseases, including type 2 diabetes and cardiovascular disease. We have therefore used monosaccharide analysis to compare cell wall polysaccharides in polished grain of a diversity panel of 370 rice lines, showing that DF varies in amount (by over three-fold) and in composition. The water unextractable (WU) non-starch polysaccharides (NSP) comprise up to 99.6% of total NSP with galacturonic acid and galactose being the most abundant monosaccharides. Correlation analysis of individual monosaccharides predicted pectin, arabinogalactan and glucurono(arabino)xylan as the dominant polysaccharides. Hierarchical clustering analysis (HCA) and principal component analysis (PCA) were used to classify the lines into 10 groups which differed in both total amount and composition of NSP. This identified a small group of lines with high contents of WU NSP which may be exploited to develop new rice cultivars with high contents of DF in polished grain, reducing the risk of chronic diet-related diseases. Graphical abstract: Image 1 Highlights: Dietary fibre (DF) was analysed in 370 genotypes of polished rice. Substantial variation in DF content and composition was demonstrated. Water unextractable DF accounts for over 96% of total non-starch polysaccharides. Pectin, arabinogalactan and xylan are major polysaccharides. The variation should be amenable to exploitation to develop improved rice cultivars.